Sanitary and physiological quality of seeds of Acca sellowiana (O. Berg) Burret - Mateus Alves Saldanha; Marlove Fátima Brião Muniz; Clair Walker; Alexsandra Cezimbra Quevedo; Vinícius Spolaor Fantinel (Agro@mbiente On-line, 2020)
Goiaba-serrana, a fruit species native to the southern region of Brazil, is promising in ecological and commercial terms. The species propagates naturally through sexual (seeds); however, it may be produced by cutting, grafting, and micropropagation. Several fungal genera can be associated with seeds and be transmitted to seedlings. Thus, this study aimed to identify fungal genera and to analyze different substrates for the germination of Acca sellowiana, associated with seeds from a different origin. To evaluate the microorganisms associated with the seeds, the method of incubation on a paper substrate (“blotter test”) was used. The germination test was carried out in a completely randomized design, in a factorial scheme, (2 x 4), with 4 repetitions of 25 seeds per substrate and lot. The factors corresponded to two origin (Serafina Corrêa and Vacaria, state of Rio Grande do Sul) and four substrates (sand, paper roll, on paper and vermiculite). The fungal genera associated with goiaba-serrana seeds were: Penicillium spp., Aspergillus spp. and Trichoderma spp. The sanity test showed the origin influences the incidence of fungi in the seeds and physiological quality. Moreover, the origin of Serafina Corrêa presented better physiological quality in relation to the Vacaria lot. Any of the substrates used can be used for the germination of goiabaserrana seeds.